FEEDBACK EXPRESSIONS USED BY AN ENGLISH TEACHER OF TOUR AND TRAVEL DEPARTMENT - Wasding, Ratnah (Universitas Pendidikan Indonesia, 2013)
Abstract: Feedback as a part of teacher talk plays a crucial role in language learning. Feedback not only gives reinforcement to maintain good behaviors of the students but also makes students aware of the mistake they make during the learning and teaching process so that they are able to revise it. This study aims to identify the types of feedback expressions used by the teacher in teaching learning process, both positive and corrective feedback. The focus of the study was on the oral teacher feedback. To gather the data, one English teacher and her students who were studying English as a foreign language were observed while they were in a teaching learning process. Their interactions in the classroom were recorded, transcribed, and then analyzed to find out the types of feedback expressions used by the teacher during the interaction. The finding revealed that the teacher used both positive and negative feedback in the teaching and learning process. In terms of positive feedback, the teacher mostly used repetition, followed by praise and affirmation. In terms of negative feedback, the teacher also used a variety of ways which include repetition as the most common feedback provision, followed by recast, clarification request, elicitation, explicit correction, and prompting.